S STRATEGI KEPALA SEKOLAH DALAM IMPLEMENTASI PROGRAM SEKOLAH PENGGERAK DI SMP NEGERI 3 KAYUAGUNG - Doni, Doni Gunawan; Bukman, Bukman Lian; Nuril, Nuril Furkan (EduTeach : Jurnal Edukasi dan Teknologi Pembelajaran, 2025)
The “Sekolah Penggerak” Program is a government effort to realize the vision of sovereign, independent, and individual Indonesian education through the creation of “Pelajar Pancasila”. This study aims to describe and analyze the principal's strategy in implementing the “Sekolah Penggerak” program at SMP Negeri 3 Kayuagung. Data collection used interviews, observations, and documentation. Data were analyzed using interactive model analysis techniques from Miles and Huberman. The results of this study show the principal's strategy in implementing the “Sekolah Penggerak” program, namely (1) strengthening human resources, (2) learning management based on a differentiated learning approach, (3) providing supporting facilities and infrastructure for the “Sekolah Penggerak” program, (4) financing by optimizing financing sources from school operational assistance funds and financing from stakeholders, (5) the process of digitizing schools such as digitizing teaching materials, teacher teaching administration, increasing school internet capacity and speed, and providing computer devices for the learning process, and (6) stakeholder involvement in program preparation, implementation and supervision of this program.